The processes involved in mentally constructing event- and scene-based autobiographical representations. Issue 3 (3rd April 2019) - Sheldon, Signy; Cool, Kelly; El-Asmar, Nadim
ABSTRACT: Autobiographical experiences can be mentally constructed as generalised events or as spatial scenes. We investigated the commonalities and distinctions in using episodic and visual imagery processes to imagine autobiographical scenarios as events or scenes. Participants described personal scenarios framed as future events or spatial scenes. We analyzed the number and type of episodic details within the descriptions. To measure imagery processing, we monitored eye-movements and examined the impact of viewing a imagery disrupting stimulus (Dynamic Visual Noise; DVN) when these descriptions were made. We found that events were described with more generalised details and scenes with more perceptual details. DVN reduced the number of episodic details generated for all descriptions and eye fixation rates negatively correlated with the number of these details that were generated. This suggests that different content is used to imagine event- or scene-based experiences and imagery contributes similarly to the episodic specificity of these imaginations.